Sarcopenia in a Multiethnic State: A Cross-Sectional Data Analysis of Multicentre Indonesia Longitudinal Aging Study - Kuntjoro Harimurti; Siti Setiati; Czeresna Heriawan Soejono; IGP Suka Aryana; Sri Sunarti; Fatichati Budiningsih; Roza Mulyana; Lazuardhi Dwipa; Agus Sudarso; Rensa Rensa; Rahmi Istanti; Muhammad Khifzhon Azwar; et al. (Interna Publishing, 2023)
Background: Previous regional studies related to sarcopenia in multiethnic Indonesia suggested inconsistent findings. We aimed to find the prevalence of sarcopenia and its associated factors among Indonesian older adults. Methods: In this cross-sectional analysis, we utilised the data of Indonesia Longitudinal Aging Study (INALAS) from community-dwelling outpatients in eight centres. Statistical analyses included descriptive, bivariate, and multivariate analyses. We categorised older adults into sarcopenia group based on the criteria of the SARC-F questionnaire, namely strength, assistance with walking, rising from a chair, climbing stairs, and falls questionnaire. Results: Among 386 older adults, 17.6% were in sarcopenia group. The prevalence of sarcopenia was found to be the lowest in Sundanese group (8.2%). Following appropriate statistical adjustment, sarcopenia was associated with female sex (OR 3.01, 95% CI 1.34-6.73), dependent functional capacity (OR 7.38, 95% CI 3.26-16.70), frailty (OR 11.82, 95% CI 5.41-25.80), and history of fall (OR 5.17 (95% CI 2.36-11.32). Sarcopenia was not significantly associated with age 70 years and older (OR 1.67, 95% CI 0.81-3.45), Sundanese group (OR 0.44, 95% CI 0.15-1.29), and being at high risk for malnutrition or malnourished (OR 2.98, 95% CI 0.68-13.15). All centenarians had no sarcopenia nor frailty, and 80% of them were Sundanese older adults. Conclusion: One in five Indonesian community-dwelling older adults had sarcopenia, associated with female sex, dependent functional capacity, frailty, and history of fall. Albeit statistically nonsignificant, there may still be link between Sundanese, age 70 years and older, as well as being at high risk for malnutrition, and sarcopenia.